THE EFFECT OF GIVING INCENTIVES TO EMPLOYEE PERFORMANCE PT. BPR EKADHARMA MAGETAN - Wahna Widhianingrum (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
The problem in this study is whether the provision of incentives significantly affects the performance of employees at PT. BPR Ekadharma Magetan. The purpose of this study is to determine whether there is an effect of giving incentives to employee performance. The type of research used is quantitative with an associative approach. The technique of collecting data through observation, questionnaires and documentation. While the data analysis technique used is simple linear regression. As for the types of data sources, this research is primary data, namely data obtained directly from the source or place where the research was conducted. The population of this research is all employees and managers of PT. BPR Ekadharma Magetan totaling 93 people. The sample determination is saturated sampling. Data obtained using SPSS 21 (Statistical Product and Service Solutions). The results of this study indicate that based on the results of research that researchers conducted at PT. BPR Ekadharma Magetan that giving incentives has a significant effect on employee performance. This can be seen from the results of statistical calculations through partial hypothesis testing which shows that t count > t table then Ha is accepted and Ho is rejected. Keywords: Incentives, Employee Performance